COMPARATIVE FOLIAR MICROMORPHOLOGICAL STUDIES OF SOME SPECIES OF ASTERACEAE FROM ALPINE ZONE OF DEOSAI PLATEAU, WESTERN HIMALAYAS - Bano; M. Ahmad; M. Zafar; S. Sultana; M. A. Khan (Journal of Animal and Plant Sciences, 2015)
This study concerns the evaluation of foliar epidermal anatomical characteristics of twelve species of Asteraceae by light microscopy (LM). The plant materials were collected from various localities of Deosai plateau. Three stomata types including anisocytic, actinocytic and anomocytic have been found in the family. Stomata type is Anisocytic in Artemisia persica, Actinocytic in Circium falconerii and Erigeron multiradiatus while anomocytic in rest of the nine species. The stomata type seems to be constant character at genus level. Leaf epidermal features like shape of epidermal cells and trichomes are found useful taxonomic tools. The epidermal cells were irregular or polygonal with straight or undulate walls. Two species of Saussurea viz., Saussurea nepalensis and S. obvallata are distinguishable on the basis of shape of epidermal cells. The pattern of walls is similar on both abaxial and adaxial sides in all species except in Senecio chrysanthemoides where it is weakly undulate on abaxial side and heavily undulate on adaxial side. The diversity in the foliar trichomes is of taxonomic importance for discrimination of taxa at specific level. Artemisia persica was unique in being the only species with stellate trichome. Aster himalaicus can be delimited from other species by the possession of J-shaped trichomes while long multicellular trichomes were found in Conyza japonica and Senecio chrysanthmoides. The results of foliar micromorphological features were comparatively described and quantitative parameters were also presented which proved to be helpful for differentiation of selected species.
Keywords: Foliar epidermal anatomy; Asteraceae; Deosai plateau